2018
DOI: 10.1111/1759-7714.12844
|View full text |Cite
|
Sign up to set email alerts
|

Presence of few PD‐1‐expressing tumor‐infiltrating immune cells is a potential predictor of improved response to salvage chemotherapy following nivolumab for non‐small cell lung cancer: An exploratory case series

Abstract: BackgroundThe combination of PD‐1 inhibitors and cytotoxic drugs is reported to enhance anti‐tumor activity in non‐small cell lung cancer; however, the underlying synergistic mechanisms remain uncertain. This retrospective case series was designed to investigate objective response and survival rates of salvage chemotherapy following nivolumab and explore the immunohistochemical profiles of tumor‐infiltrating immune cells.MethodsThe medical records of 37 patients administered nivolumab were retrospectively revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…In addition, disease progression during first‐line chemotherapy for NSCLC was reported to correlate with high levels of circulating MDSCs . Combining these findings with the results of our previous studies, we hypothesize that both the exhaustion levels of cytotoxic T cells and interference with myeloid cells may affect the efficacy of nivolumab and subsequent salvage chemotherapy (Fig ).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…In addition, disease progression during first‐line chemotherapy for NSCLC was reported to correlate with high levels of circulating MDSCs . Combining these findings with the results of our previous studies, we hypothesize that both the exhaustion levels of cytotoxic T cells and interference with myeloid cells may affect the efficacy of nivolumab and subsequent salvage chemotherapy (Fig ).…”
Section: Discussionsupporting
confidence: 75%
“…In contrast, our previous studies showed that the presence of a few PD‐1 + TILs was associated with the response to salvage chemotherapy, as well as nivolumab treatment . However, we did not clarify why preceding nivolumab therapy showed less antitumor activity in the responders to salvage chemotherapy.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations